Simplified design of elastoplastic structures with metallic yielding dampers based on the concept of uniform damping ratio. (1st December 2018) - Zhang, Ruifu; Wang, Chao; Pan, Chao; Shen, Hua; Ge, Qingzi; Zhang, Luqi
Highlights: Uniform damping ratio design concept is raised for structure with metallic dampers. Dampers are expected to have the same damping ratio under certain dynamic excitations. Stiffness and damping parameters of metallic dampers can be designed individually. Design procedure can be simplified with a demand-oriented design scheme based on UDR. Elastoplastic properties of both the structure and dampers are considered. Abstract: This study proposes a novel design concept, referred to as the uniform damping ratio (UDR) concept, to improve the seismic energy dissipation efficiency of damped structures with metallic yielding dampers (MYDs) by maximizing the use of the capability of each damper. Furthermore, this new concept can simplify the design procedure of structures with MYDs. The UDR concept implies that all installed MYDs have the same equivalent damping ratio under dynamic excitations, which enables each MYD to be fully utilized. The UDR concept can simplify the estimation process of the additional equivalent damping ratio of a damped structure and decouple the stiffness and damping effects caused by MYDs, which can be designed separately. A performance demand-oriented design procedure is presented based on the UDR concept considering the nonlinear properties of an original structure and MYDs under an intense earthquake. The design procedure involves the following three steps: (1) determine seismic performance demand and obtain the elastic and elastoplastic properties of the original structure using pushover analysis; (2) determine key design parameters based on the formulae derived under the UDR concept; (3) verify seismic performance via nonlinear dynamic analyses. In addition, a few empirical suggestions are provided for determining the key design parameters more efficiently. A nine-story steel frame structure with MYDs is used to exemplify the UDR-based design procedure. The seismic performance demand of the structure with designed MYDs is achieved, and the energy dissipation capacity of all installed MYDs is sufficiently utilized. The proposed UDR concept is found to be effective, and the procedure based on this concept is efficient and simple.